Evaluation of factors with potential influence on [18F]FDG radiochemical synthesis yield - Chochevska, Maja; Velichkovska, Maja; Atanasova Lazareva, Marija; Kolevska, Katerina; Jolevski, Filip; Razmoska, Jasmina; Filipovski, Zlatko; Nikolovski, Sasho; Zdraveska Kochovska, Marina; Ugrinska, Ana (Elsevier BV, 2023)
[18F]FDG radiopharmaceutical production is performed with automatic synthesis modules, which enables to carry out the production process safely, reliably and reproducibly. This study aimed to investigate the factors which may influence and give inconsistent radiochemical synthesis yield, as well as common pitfalls in the synthesis process which can occur. We evaluated more than 500 batches in the overall study. The results confirmed that irradiation parameter affect the production yield of the final product, also transport capillary capability and some synthesis factors have an impact on [18F]FDG radiochemical synthesis yield.
Keywords: Fluorine-18; Radiosynthesis; Yield; Radioactivity; Pitfalls